Application of the Artificial Bee Colony Algorithm for Solving the Set Covering Problem. (16th April 2014) - Crawford, Broderick; Soto, Ricardo; Cuesta, Rodrigo; Paredes, Fernando
Abstract : The set covering problem is a formal model for many practical optimization problems. In the set covering problem the goal is to choose a subset of the columns of minimal cost that covers every row. Here, we present a novel application of the artificial bee colony algorithm to solve the non-unicost set covering problem. The artificial bee colony algorithm is a recent swarm metaheuristic technique based on the intelligent foraging behavior of honey bees. Experimental results show that our artificial bee colony algorithm is competitive in terms of solution quality with other recent metaheuristic approaches for the set covering problem.